Peran Bahasa Indonesia dalam Penyusunan Dokumen Bantuan Hukum di Lembaga Bantuan Hukum - Dali, Meilina Widya; Manangin, Rifangga; Halim, Andriyani; Mooduto, Nur Asivah; Kobandaha, Wulandari; Naue, Raisatun Nisa Tifany; Pilomonu, Nadifa H; Hasan, Stevie Ramadhani K; Rauf, Nur Arafah H; Yusuf, Abdulrauf; Rumpabulu, Muhammad Rifky; Yatu, Febrian; Akutali, Haikal (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to analyze the role of the Indonesian language in the preparation of legal documents at the Legal Aid Institute of the Faculty of Law, Universitas Negeri Gorontalo, and its implications for clients’ understanding and interpretation as lay members of society. This research employs a qualitative method with a descriptive approach. Data were collected through in-depth semi-structured interviews with the Head of the Legal Aid Institute and analyzed using thematic analysis. The findings indicate that the use of standard, accurate, and legally appropriate Indonesian significantly affects the clarity and effectiveness of legal aid documents. However, differences in the meaning of legal terms between the Kamus Besar Bahasa Indonesia (KBBI), statutory regulations, and public understanding often create potential ambiguity in document interpretation. Therefore, the Legal Aid Institute plays a crucial role in verifying, simplifying, and explaining legal language to ensure clients’ comprehension without diminishing its normative substance. This study confirms that the quality of Indonesian language use in legal aid documents is a key factor in ensuring legal certainty and enhancing access to justice for the community.